Social Media as an Actuating Factor in Language Learning - S.T. Sreenidhi,; Dr. P. Sathya, (International Journal of Scientific Research in Science and Technology, 2024)
Teachers with the inclusion of technology in education have upgraded their classes with progressive teaching - learning methods and tools. Along with these, a language teacher unlocks learners’ attitude and aptitude towards the language for effective learning. Stephen Karshen’s ‘The Affective Filter’ hypothesis states the factors such as motivation, self-confidence, anxiety, etc. impacts the language learning process. Hence, language teachers apart from teaching a language they also help the learners to overcome their anxiety towards a second or foreign language with proper support, guidance and motivation. Social Media platforms are a part of every individual today, it creates and provides space to teach, play and use any language flexibly. Simultaneously, it consciously and unconsciously motivates its users to use the language, to commit mistakes and rectify them, by sharing the opportunities and obstacles in the common platforms. Social media has visualized the inner anxiety of an individual and its outcomes to the learners. It further pushes them to accept the reality and to overcome their anxiety. This paper is an attempt to highlight the role of social media as an actuating factor among the language learners.
Keywords: Social Media; Affective Filter; Actuating Factor; Technology; Unconscious Process